Visualization and Estimation of 0D to 1D Nanostructure Size by Photoluminescence - Artūrs Medvids; Artūrs Plūdons; Augustas Vaitkevičius; Saulius Miasojedovas; Patrik Ščajev (Nanomaterials)
We elaborate a method for determining the 0D–1D nanostructure size by photoluminescence (PL) emission spectrum dependence on the nanostructure dimensions. As observed, the high number of diamond-like carbon nanocones shows a strongly blue-shifted PL spectrum compared to the bulk material, allowing for the calculation of their top dimensions of 2.0 nm. For the second structure model, we used a sharp atomic force microscope (AFM) tip, which showed green emission localized on its top, as determined by confocal microscopy. Using the PL spectrum, the calculation allowed us to determine the tip size of 1.5 nm, which correlated well with the SEM measurements. The time-resolved PL measurements shed light on the recombination process, providing stretched-exponent decay with a τ0 = 1 ns lifetime, indicating a gradual decrease in exciton lifetime along the height of the cone from the base to the top due to surface and radiative recombination. Therefore, the proposed method provides a simple optical procedure for determining an AFM tip or other nanocone structure sharpness without the need for sample preparation and special expensive equipment.